TECHNOLOGICAL ASPECTS OF STUDENTS’ INDEPENDENT LEARNING ACTIVITY INDIVIDUALIZATION IN THE PROCESS OF STUDYING HIGHER MATHEMATICS - Buhra, A. (Physical and Mathematical Education, 2021)
Problem formulation. In the conditions of rapid growth of information the process of professional qualities formation and abilities of future specialists should take place during life. Continuing education is a system-forming component of the educational paradigm of European countries. In this context, the independent work of students, as an important form of educational process must become its basis. The issue is becoming more significant for students of higher education institutions of technical profile taken into consideretion the rapid development of science, technology and engineering. This, at the same time, actualizes the problem of improving independent learning activities, one of the ways to solve which we consider in its individualization.Materials and methods. The author's experience in implementing and ensuring the process of individualization of students’ independent learning activities during the teaching of higher mathematics is used. The analysis of scientific-pedagogical and scientific-methodical literature is carried out.Results. The main technological aspects of students’ independent learning activities individualization in higher education institutions of technical profile by their perception of lecture material and tutorial-practical classes in mathematics are considered in the article. The algorithm of using the technolog presented in the form of "Mind map" during lectures which promotes the development of students' ability to apply learning outcomes creatively is reasoned.Conclusions. Analysis of the effectiveness of students’ independent learning activities individualization proves the need for its application in the study of mathematical disciplines. However, the above methods do not highlight the full range of tutor’ spossibilities. We consider the expansion of the range of methodological techniques and their didactic possibilities definition as one of the vectors of further research.
Keywords: learning individualization; independence; lecture; students of higher education institutions of technical profile